Implementasi Nilai Pancasila Ke-2 dalam Penggunaan Kecerdasan Buatan pada Platform Kesehatan SatuSehat - Supriyadi, Thomas Bedha Rosario; Ratna Endang Widuatie; Najwan Azhim Muntazhar Anas; Ester Desiana; Victoria Chelsi Surya Bandur; Iib Robiatul Adawiya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The use of Artificial Intelligence (AI) in the SatuSehat health platform is growing and demands the application of ethical principles aligned with humanitarian values. This study aims to analyze the implementation of the value of